Study on entrepreneurial attributes and traits. - Koh, Melvin Choon Suen. (2008)
Using survery data collected, this study seeks to establish the common personal and situational factors affecting the local entrepreneurs and how these factors contributes to their success. From the analysis, recommendations for a more conducive environment to nurture entrepreneurs as well as possible future studies were also made.